2005
DOI: 10.1136/hrt.2003.028092
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischaemia and the inflammatory response: release of heat shock protein 70 after myocardial infarction

Abstract: Objectives: To test the hypothesis that heat shock protein (Hsp) 70 may be released into the circulation after acute myocardial infarction (AMI) by exploring the kinetics of Hsp70 release and the relations between Hsp70 and markers of inflammation and myocardial damage in AMI. Design: Blood samples from 24 patients were prospectively collected through to the first day after AMI. Hsp70, interleukin (IL) 6, IL-8, and IL-10 in serum were measured by enzyme linked immunosorbent assay (ELISA). Results: Median Hsp70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
107
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 40 publications
5
107
2
5
Order By: Relevance
“…Increased levels of HSP70 were significantly associated with risk and disease severity in acute coronary syndrome (Zhang et al 2010). HSP70 was rapidly released into the circulation after myocardial infarction and the HSP70 levels correlated with the levels of troponin T and creatine kinase MB (Dybdahl et al 2005).The present study is similar, because in the background of cardiac arrest acute myocardial infarction was established in 85 % of patients, confirming that HSP70 is rapidly elevated after myocardial injury. Finally, elevated serum HSP70 levels in patients with severe traumatic brain injury were shown to predict poor outcomes (da Rocha et al 2005).…”
Section: Discussionsupporting
confidence: 75%
“…Increased levels of HSP70 were significantly associated with risk and disease severity in acute coronary syndrome (Zhang et al 2010). HSP70 was rapidly released into the circulation after myocardial infarction and the HSP70 levels correlated with the levels of troponin T and creatine kinase MB (Dybdahl et al 2005).The present study is similar, because in the background of cardiac arrest acute myocardial infarction was established in 85 % of patients, confirming that HSP70 is rapidly elevated after myocardial injury. Finally, elevated serum HSP70 levels in patients with severe traumatic brain injury were shown to predict poor outcomes (da Rocha et al 2005).…”
Section: Discussionsupporting
confidence: 75%
“…EGR-1 mediates the synthesis and release of HSP70 into the extracellular environment (46). In response to stressors such as myocardial infarction, HSP70 is released into the circulation and promotes the increase of TLR4 levels in patients, thereby triggering NF-kB signaling and proinflammatory cytokine production (52,53). Further studies are thus needed to elucidate the roles of extracellular mediators such as HSP in EGR-1-associated proinflammatory chemokine production in response to Nod2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…One day after AMI, the elevated Hsp70 levels showed a moderate positive correlation with IL-6 and IL-8, with TNF-α and the levels of the Toll like receptor 4, although the association was absent in healthy control subjects. Circulating Hsp70 levels were positively related to markers of myocardial damage including cardiac troponin T and creatine kinase MB (Dybdahl et al 2005;Satoh et al 2006). Hsp70 can be released into the extracellular environment not only in response to tissue damage but also under physiologic conditions (Pockley et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognised that Hsp70 are present in the peripheral circulation of healthy individuals (Pockley et al 1998;Dhingra et al 2006), and their levels increase after intensive exercise (Febbraio et al 2002;Fehrenbach et al 2005). Elevation of serum Hsp70 was reported in patients with soft tissue trauma (Pittet et al 2002;Flohe et al 2007), with peripheral and renal vascular disease (Wright et al 2000), after acute myocardial infarction (AMI; Dybdahl et al 2005;Satoh et al 2006), or coronary artery bypass grafting (Dybdahl et al 2002), preeclampsia (Molvarec et al 2006) and haemolytic anemia elevated liver enzymes low platelet count (HELLP) syndrome (Molvarec et al 2007). Genth-Zotz et al (2004) found elevated serum Hsp70 levels in CHF patients and a correlation between the Hsp70 and disease severity and cachexia, but not with survival.…”
Section: Introductionmentioning
confidence: 99%